FORMATION OF INFORMATION AND DIGITAL COMPETENCE OF STUDENTS IN THE CONTEXT OF DIGITALIZATION OF PEDAGOGICAL EDUCATION - Sopina, Olha (Sworld-Us Conference proceedings, 2025)
The article deals with the processes of implementing new educational state standards on a competency-based basis with a forecast for the learning outcome (mastery of information and digital competence by a graduate of an educational institution). The stud